Investigating pathways for agricultural innovation at scale: Case studies from India - Khandelwal, A.; Agarwal, N.; Jain, B.; Gupta, D.; John, A.T. (Commission on Sustainable Agriculture Intensification, 2022)
This is one of three country studies on Innovation Pathways in Agri-food Systems, managed by the Commission for Sustainable Agriculture Intensification (CoSAI). The three studies use a common analytical framework to generate lessons on factors leading to successful innovation pathways, to guide future investment.